Utilizing small molecules to probe and harness the proteome by pooled protein tagging with ligandable domains - Larrimore, Katherine E.; Serebrenik, Yevgeniy V. (Frontiers in Pharmacology, 2025)
Multifunctional ligand-binding domains have revolutionized cell biology by enabling the precise visualization and manipulation of fused proteins of interest through small molecule probes. Employing these domains is labor-intensive and low-throughput, limiting studies to only small subsets of proteins at a time. However, advancements in high-throughput technologies like pooled protein tagging have enabled the tagging of proteins across the entire proteome with ligand-binding domains. This allows for the generation of complex cell libraries where each cell expresses a different protein fused to a generic, ligandable handle. These libraries unlock opportunities to explore the proteome with a versatile toolbox of small molecule probes designed to interact with the fused tags, allowing researchers to visualize protein localization, induce protein misfolding, manipulate protein-protein interactions, modulate protein stability, and more in a scalable, systematic manner. This review explores recent studies employing multifunctional domains at proteome scale, delving into how the associated chemical probes have been employed to enable insights into endogenous protein function, cellular processes, and disease mechanisms. Additional multifunctional ligand-binding domains are discussed that can be used in pooled protein tagging, as well as their potential strengths and weaknesses. We also discuss potential applications in drug discovery such as high-throughput screening for therapeutic targets with insights for bifunctional ligand optimization. By integrating pooled protein tagging with ligand-binding domains and chemical probes, we highlight how the fusion of chemical biology and functional genomics is paving the way for innovative research avenues and transformative advances in cell biology and pharmacology.